Glucose deprivation promotes apoptotic response to S1 by enhancing autophagy in human cervical cancer cells - Zhou L; Kong QH; Zhang YH; Yang W; Yan S; Li MH; Wang YD; Zhou YJ; Yu HM; Han LY (Cancer Management and Research, 2018)
Li Zhou,1,2 Qinghuan Kong,3 Yunhan Zhang,3 Wei Yang,4 Shan Yan,3 Meihui Li,3 Yidan Wang,3 Yanjie Zhou,3 Huimei Yu,3 Liying Han1 1Department of Obstetrics and Gynecology, The Second Hospital of Jilin University, Changchun 130041, China; 2Department of Obstetrics and Gynecology, The First Hospital of Jilin University, Changchun 130021, China; 3Department of Pathology and Pathophysiology, School of Basic Medical Sciences, Jilin University, Changchun 130021, China; 4Department of Hepatobiliary and Pancreatic Surgery, The First Hospital of Jilin University, Changchun 130021, China Background: S1 is a novel BH3 mimetic that can induce death in some types of cancer cells, such as melanoma B16, ovarian cancer SKOV3, and U251 glioma cells. S1 inhibits Bcl-2 and Mcl-1 expression and induces cancer cell apoptosis. Cancer cell survival is highly dependent on glucose. Here, we observed the effect of glucose deprivation on the apoptotic response to S1 in human cervical cancer (HeLa) cells.Materials and methods: Earle’s balanced salt solution (EBSS) was used to simulate glucose deprivation. MTT assay was used to analyze the cell survival rate, and Hoechst 33342 dye was used to detect the apoptosis in HeLa cells. Western blotting was used to detect the expression of ER stress and autophagy relative proteins. In addition, lysosomes were observed with LysoTracker staining by confocal microscopy.Results: S1 decreased cell distribution density and survival rate, and MTT assay showed that EBSS enhanced the inhibitory effects of S1 on HeLa cell growth. Hoechst 33342 dye showed that S1 led to pyknosis, fragmentation, and strong staining in HeLa cell nuclei, and EBSS enhanced these effects. Western blotting indicated that EBSS enhanced the expression of apoptosis-related proteins (cytochrome C, caspase-3, and poly[ADP-ribose] polymerase 1) induced by S1 in HeLa cells. S1 decreased p62 expression and increased the autophagosome-associated protein LC3-II expression, which indicated that S1 induced autophagy in HeLa cells. EBSS enhanced S1-induced autophagy in HeLa cells. Furthermore, autophagy inhibitor chloroquine enhanced S1-induced apoptosis in HeLa cells.Conclusion: These results indicate that EBSS exacerbates S1-induced autophagy and severe autophagy induced by EBSS and S1 could lead to apoptosis in HeLa cells. The results also suggest that EBSS enhances the sensitivity of HeLa cells to S1-induced apoptosis and that autophagy plays an important role in this process. Keywords: Earle’s balanced salt solution, glucose deprivation, S1, endoplasmic reticulum stress, autophagy, apoptosis